Coherent crystal branches: the impact of tetragonal symmetry on the 2D confined polymer nanostructure - Ziying Liang; Nan Zheng; Bo Ni; Ziwei Lai; Hui Niu; Shuailin Zhang; Yan Cao (IUCrJ, 2021)
The symmetry of polymer crystals greatly affects the optical, thermal conductivity and mechanical properties of the materials. Past studies have shown that the two-dimensional (2D) confined crystallization of polymer nanorods could produce anisotropic structures. However, few researchers have focused on understanding confined nanostructures from the perspective of crystal symmetry. In this research, we demonstrate the molecular chain self-assembly of tetragonal crystals under cylindrical confinement. We specifically selected poly(4-methyl-1-pentene) (P4MP1) with a 41 or 72 helical conformation (usually crystallizing with a tetragonal lattice) as the model polymer. We found a coherent crystal branching of the tetragonal crystal in the P4MP1 nanorods. The unusual 45°- and 135°-{200} diffractions and the meridional 220 diffraction (from 45°-tilted crystals) have shown a uniform crystal branching between the a1-axis crystals and the 45°-tilted crystals in the rod long axis, which originates from a structural defect associated with tetragonal symmetry. Surprisingly, this chain packing defect in the tetragonal cell can be controlled to develop along the rod long axis in 2D confinement.